Behavioral observations in a capybara colony (Hydrochoerus hydrochaeris) - Murphey, Robert M.; Mariano, Jorge S.; Moura Duarte, Francisco A. (Applied Animal Behaviour Science, 1985)
Capybaras (Hydrochoerus hydrochaeris), the largest living rodents, are receiving increasing interest as an economically attractive source of meat and hides in tropical America. An unmanaged capybara colony was studied in a setting adjacent to agricultural activities in Brazil. Preliminary notes were made on alarm responses to intruders, various aspects of flight behavior, and investigatory activity. The findings were mostly consistent with studies carried out by other investigators, suggesting that capybara behavior is similar from one region to another. The animals have potential for habituation to humans and are probably good candidates for domestication. Expanded commercial exploitation of capybaras could benefit their survival and welfare as well as contributing to the preservation of neotropical ecology in general. © 1985.